William Wallace : the true story [videorecording (DVD)] - Ferguson, Jock; Carruthers, Bob; Kinnaird, David (Heroes of Scotland., 2006)
The powerful story of the Scottish Patriot, who never faltered in his struggle against English oppression, is retold with stunning battle footage, reconstructions and re-enactments.